Analisa Sufistik Mimpi Nubuwwah dalam Proses Kenabian - Satriawan, Lalu Agus (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2011)
This article tries to scrutinize dreams as prophetic command (nubuwwah) and happy news (mubashshirât) from Allah. The article describes the concept of prophethood, the concept of sainthood, the relation between prophethood and sainthood, and dreams as a part of prophethood. The article uses interpretation method. Prophetic dreams are dreams where spiritual impressions are directly reflected by heart without any intervention from the imagination. Dreams can be acquired and accessed with self purification through mujâhadah al-nafs.